(untitled) (LEARNing Landscapes, 2013)
This paper asserts that through the process of observation, documentation, and interpretation of children’s goals, strategies, and theories, teachers gain insight into children’s thinking. As a result of this process, teachers are better able to engage children in conversations and investigations that have the potential to extend their learning in both depth and breadth. Utilizing brief video clips of both children and adults to support its premise, the paper outlines and discusses relevant aspects of observation for understanding and introduces the concept of the videative as a powerful resource for revisiting and analyzing documented observations.